Identification by HPLC of Undeclared Active Ingredients in Aphrodisiac Teas and Coffees Sold in Kinshasa and Kisangani (DRC) - ADONIO, Tresor; Kalonda, S.; Marini, R. D.; Mbinze, K. J. (Orapuh Journal, 2025)
IntroductionThis study aims to identify the presence of undeclared active ingredients in aphrodisiac products sold as teas and coffees in Kinshasa and Kisangani (DRC). Sexual dysfunction is widespread, and many individuals in the Democratic Republic of the Congo rely on aphrodisiac teas and coffees. However, their unregulated nature raises concerns about adulteration with undeclared substances (sildenafil and tadalafil) and potentially harmful compounds (aristolochic acid), posing significant health risks.Purpose To detect, by HPLC, the presence of PDE‑5 inhibitors (sildenafil, tadalafil) and toxic compounds (aristolochic acid) in aphrodisiac products marketed without regulation.Methods Nine samples, including seven from Kinshasa and two from Kisangani, were analysed by HPLC after sample‑preparation protocols adapted from validated studies.Results Sildenafil was detected in 9/9 products and tadalafil in 8/9; traces of aristolochic acid were identified in two products. Quantitative variation suggests deliberate adulteration.ConclusionThese products contain undeclared and potentially harmful substances, posing a significant health risk such as cardiovascular complications, drug interactions, and possible carcinogenic effects, underscoring the urgent need for stricter regulation.